Interpersonal Communication Strategy on Employee Adaptation and Performance at Pt Pertamina Lubricants Sales Region I Sumbagut - Ivana, Rima; Lubis, Lusiana Andriani; Pohan, Syafruddin (East Asian Journal of Multidisciplinary Research, 2024)
The purpose of this research is to analyze the influence of interpersonal communication on adaptation, to analyze the influence of interpersonal communication on employee performance. The research method used is descriptive quantitative. The population consists of active employees of PT Pertamina Lubricants (PTPL) Sales I Region SUMBAGUT, with a total sample of 50 respondents taken through total sampling at PTPL Sales Region I SUMBAGUT in 2024. Data analysis was performed using single tables, cross tables, t-test, and the Coefficient of Determination. The results showed Interpersonal Communication Strategies resulted in four strategies: 1). SO (Strength-Opportunity) Strategy by enhancing interactive communication between employees and supervisors to utilize supervisors who openly accept employee feedback, 2). ST (Strength-Threat) Strategy by developing interactive communication to overcome difficulties in discussing work issues with supervisors, 3). WO (Weakness-Opportunity) Strategy by improving communication among employees by leveraging supervisors who openly accept feedback, and 4). WT (Weakness-Threat) Strategy by developing two-way communication to overcome difficulties in speaking and obtaining support from supervisors.